Surface enhanced 3D rGO hybrids and porous rGO nano-networks as high performance supercapacitor electrodes for integrated energy storage devices. (March 2020) - Kiran, Sarigamala Karthik; Shukla, Shobha; Struck, Alexander; Saxena, Sumit
Abstract: Rapid advancements in technology has led to urgent requirement for mobile and portable power sources. Achieving self-sustainability using renewable energy sources using such devices provide an added advantage. Electrode materials play a critical role in performance of these devices, while the surface morphology of the electrode material play a crucial role in performance of electrodes themselves. Here we report fabrication of a flexible, all-solid state high performance hybrid supercapacitor using the 3D dendritic cell like nanostructures of Ni–Co LDH@rGO as cathode and novel crumpled leaf like rGO nano porous networks as anode. PVA-KOH gel is used as solid-state gel electrolyte. The fabricated supercapacitor is incorporated with a solar cell to demonstrate a self sustainable power pack The working potential window obtained is ∼1.4–1.8V. The asymmetric and hybrid assembly of the device enables in achieving high energy and power density. The energy and power density of the assembled supercapacitor is ∼58.4 Wh/Kg and ∼374 W/kg respectively at a current density of 0.5 A/g. The Coulombic efficiency is approximately 100% and suggests superior performance of the supercapacitor. Our experiments demonstrate the potential use of graphene based materials for powering wearable and portable electronic devices in a self sustainable manner. Graphical abstract: Image 1